Sustainable Behavior in the Balinese Hospitality Industry: How Perceived Value and Social Psychological Distance Mediate Social Media Activity - Sari, Desak Made Febri Purnama; Meisya Venita, Putu Bella; Ayu Tirtayani, I Gusti; Suidarma, I Made (JURNAL MANAJEMEN MOTIVASI, 2026)
This study aims to examine the influence of brand awareness, brand image, and product quality on purchase decisions of Scarlett Whitening in Denpasar City. A quantitative approach was employed using a questionnaire distributed to 100 respondents. Data analysis was conducted using multiple linear regression. The results indicate that brand awareness, brand image, and product quality have a positive and significant effect on purchase decisions. The implication of this study provides valuable insights for companies to improve brand strategies and product quality in order to influence consumer purchase decisions more effectively in a competitive and dynamic market environment.